1974
DOI: 10.1159/000175537
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian, Adrenal and Litter Restriction Effects on Fetal and Placental Development

Abstract: Surgical litter restriction to one to five fetuses per rat, results in highly significant increases in fetal body and placental weight. Intrauterine crowding, competition, and the amount of nutrients available per fetus appear to be the limiting factors controlling fetal development. The interaction of ovarian and adrenal hormones was investigated by surgical removal of ovarian and adrenal tissue during litter restriction. Increased intrauterine growth does not appear to be directly controlled by the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Experimental alterations of the intrauterine environment can result in enhanced fetal development, as is the case when litter size is surgically reduced (8)(9)(10). Fetal development is dependent on blood supply, and experimental ischemia in individual fetuses resulted in restrict ed development of fetal body and brain development as reported by us (11).…”
mentioning
confidence: 99%
“…Experimental alterations of the intrauterine environment can result in enhanced fetal development, as is the case when litter size is surgically reduced (8)(9)(10). Fetal development is dependent on blood supply, and experimental ischemia in individual fetuses resulted in restrict ed development of fetal body and brain development as reported by us (11).…”
mentioning
confidence: 99%
“…Even genetic factors, controlling birth weight, can easily be obviated by the manipula tion of the internal environment directly, either to optimize fetal development as in the case of surgical litter restriction as reported by us (1,2), or to adversely effect fetal development due to experimental eclampsia (3). Manipulation of the dietary intake during pregnancy, regardless if it is protein, single amino acid, vitamin, or mineral deficiency (see review in 4), all and each one of them result in an altered fetal outcome.…”
mentioning
confidence: 99%
“…It is tempting to speculate, however, that the cause may involve the placenta. Placentas of surgically produced singleton rabbit fetuses as well as those of mice and rats from restricted pregnancies are larger than those of controls (McLaren, 1965;van Marthens & Grauel, 1974;van Marthens et al, 1972;Zambrana & Greenwald, 1971). McLaren (1965) also demonstrated that within a uterine horn a direct relationship exists between fetal and placental weight.…”
Section: Discussionmentioning
confidence: 92%
“…Just prior to term, the singletons were up to 105% heavier than controls and containing as much as 21% more cerebral DNA. Singleton rat fetuses have been shown to have elevated body, placental and brain weights (Croskerry, Smith, Hall, & Shepard, 1978;van Marthens & Grauel, 1974;Zambrana & Greenwald, 1971). Two other experiments, while not creating singletons, did examine the offspring of pregnancies for which the number of fetuses was restricted (Milkovic, Paunovic, & Joffe, 1976;van Marthens & Zamenhof, 1969).…”
mentioning
confidence: 99%